Mapping ergonomics application to improve SMEs working condition in industrially developing countries: a critical review - Hermawati, Setia; Lawson, Glyn; Sutarto, Auditya Purwandini (Taylor & Francis, 2014)
In industrially developing countries (IDC), small and medium enterprises (SMEs) account for the highest proprotion of employment. Unfortunately, the working conditions in SMEs are often very poor and expose employees to a potentially wide range of health and safety risks. This paper presents a comprehensive review of 161 articles related to ergonomics application in SMEs, using Indonesia as a case study. The aim of this paper is to investigate the extent of ergonomics application and identify areas that can be improved to promote effective ergonomics for SMEs in IDC. The most urgent issue found is the need for adopting participatory approach in contrast to the commonly implemented top-down approach. Some good practices in ergonomics application were also revealed from the review, e.g. a multidisciplinary approach, unsophisticated and low-cost solutions, and recognising the importance of productivity. The review also found that more work is still required to achieve appropriate cross-cultural adaptation of ergonomics application. Practitioner Summary: Despite continuous efforts in addressing ergonomics issues in SMEs of IDC, workers are still exposed to poor work conditions. We reviewed factual-based evidence of current ergonomics application to inform future strategies of ergonomics in IDC, using Indonesia as a case study.